Investigation of the Different Morphologies of Zinc Oxide (ZnO) in Cellulose/ZnO Hybrid Aerogel on the Photocatalytic Degradation Efficiency of Methyl Orange - Hasanpour, Maryam; Motahari, Siamak; Jing, Dengwei; Hatami, Mohammad (Topics in catalysis, 2024)
In the present study, the cellulose/zinc oxide hybrid aerogel (CA/ZnO) was successfully synthesized via different as-prepared methods. The obtained ZnO structure in CA/ZnO hybrid aerogel indicated porous hemispherical structures, cone-like, nanorod (rice grain-like shape), and flower-like morphologies. The different created structure for the as-prepared samples may be due to the different growth of zinc oxide under synthesis conditions.The as-synthesized samples were determined by X-ray diffraction (XRD), Fourier transforms infrared (FT-IR), field emission scanning electron microscopy (FE-SEM), Energy dispersive X-ray analysis (EDX), Brunauer–Emmett–Teller (BET), UV-Vis spectroscopy. Then, their effect on the removal efficiency of methyl orange (MO) solution was investigated under UV light irradiation. The BET analysis revealed that specific surface area of the as-prepared samples with using different methods was in the range of 43.70–352.82 m 2 /g. The obtained results indicated that the morphology of CA/ZnO hybrid aerogel plays a significant role in the photodegradation performance of MO. Among all as-prepared samples with different morphologies, the plate-like structure of ZnO demonstrated the maximum removal efficiency of MO (94.78%). Graphic Abstract